Sosyal Bilgiler Derslerinde Tıp Tarihi Konularının Sözlü Tarihle Öğretimi / Teaching of Medicine History Topics by Using Oral History in Social Studies Courses - Dere, İlker; Alkaya, Sevim (Journal of History Culture and Art Research, 2017)
Abstract Oral history method was proposed for the first time to develop students’ ability in perception of change and endurance under Social Studies Teaching Program held in 2005. Although there are various subjects which may be taught using oral history method in the program, the method hasn’t preferred by social studies teachers. The purpose of this study is to explore the potential of oral history method in teaching of topics of medicine history in the 2005 Social Studies Teaching Program. Action research model is utilized in present study which is one of the qualitative research methods used in social sciences. Working group consisted 22 students of 6th grade who were selected according to purposive sampling technique. Content analysis method is used for the data analysis in this reserach. The results of the study show that the students have a positive attitude towards oral history method but they do not like transcribing the audio recordings. Also, the research uncovers that oral history is an effective method in terms of comparing the past and present, learning various disasters and treatment methods in detail and bringing in perception of change and continuity. Social studies teachers who use oral history method in their classroom might determine whether the voice recordings should be transcribed or not with their students. Öz Sözlü tarih yöntemi, ilk defa 2005 Sosyal Bilgiler Öğretim Programı’nda öğrencilere değişim ve sürekliliği algılama becerisini kazandırmak için önerilmiştir. Programda sözlü tarih yönteminin kullanılabileceği birçok konu bulunmasına rağmen yöntem, sosyal bilgiler öğretmenleri tarafından yeterince tercih edilmemektedir. Bu çalışmanın amacı, sözlü tarih yönteminin 2005 Sosyal Bilgiler Öğretim Programı’ndaki tıp tarihi konularının öğretimi konusundaki potansiyelini ortaya koymaktır. Araştırma deseni olarak nitel araştırma yöntemlerinden eylem araştırması modeli kullanılmıştır. Çalışma grubu, amaçlı örneklem tekniğine göre seçilen 22 (6. sınıf) öğrenciden oluşmuştur. Elde edilen veriler, içerik analizine tabii tutulmuştur. Araştırma sonunda ulaşılan sonuçlar, öğrencilerin sözlü tarih uygulamasına ilişkin olumlu düşüncelere sahip olduğunu ancak onların ses kayıtlarını deşifre etmekten hoşlanmadığını göstermektedir. Ayrıca araştırma, sözlü tarihin geçmişle günümüzü karşılaştırma, çeşitli hastalıkları ve tedavi yöntemlerini ayrıntılı şekilde öğrenme ve değişim ve sürekliliğin algılamasında etkili bir yöntem olduğunu ortaya çıkarmıştır. Sözlü tarihi derslerinde kullanacak öğretmenlere, görüşme kayıtlarının transkript edilip edilmeyeceğine öğrencilerle birlikte karar verebilir.